Pengaruh Kualitas Pelayanan Dan Penanganan Complain Terhadap Kepuasan Pelanggan J&T Express Wilayah Asakota - M. Riaas Rasyid; Irma Mardian (Pusat Riset dan Inovasi Nasional, 2023)
In this era of globalization, business people continue to rack their brains to meet the desires and needs of consumers who are increasingly numerous and diverse. This is a challenge that business people must face to make consumers satisfied with everything they need. Not only does the manufacturing industry dominate economic activity throughout the world, but the service industry also plays an important role. One of the logistics companies that is considered the most favorite used by consumers is J & T Express. (Aprisia & Mayliza, 2017) defines service quality as a measure of how well the level of service provided meets customer expectations.